Women's Leadership in Surah An-Naml Verses 23-44 (Ma'na Cum Maghza Study) - Devi Suraya Az-Zahra; Eka Prasetiawati; Muhamad Agus Mushodiq (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Women's leadership is a topic that is receiving increasing attention in various fields, including politics, business, education and social affairs. As time goes by, women have demonstrated their capacity and competence to lead, inspire and bring about positive change. While still facing various challenges, such as gender stereotypes and inequality of opportunity, many women have proved that they are capable of being effective and visionary leaders. This article discusses women's leadership in Surah An-Naml verses 23-44, which contains the story between Prophet Sulaiman and Queen Saba’. This story allegedly provides an ideal picture of women's leadership. This research uses a library approach. Data and data sources are obtained from the Al-Qur'an surah An-Naml verses 23-44. Data collection techniques are obtained through note-taking. The analysis technique uses an interpretive descriptive approach with the hermeneutical theory ma'a cum maghza. The research results show that the figure of a female leader as stated in the story of Prophet Sulaiman and Queen Saba’ in Surah An-Naml Verses 23-44 produces the qualifications of a female leader who has social and material power, thinks open minded towards opponents or opposition, is democratic and a leader who admits mistakes and accepts the truth.